Od społecznej odpowiedzialności do edukacji. Wyzwania biznesu wobec gospodarki cyrkularnej - Filek, Janina; Stanisławska-Mischke, Anna K. (Humaniora. Czasopismo Internetowe, 2025)
The imperfections of economic activity from an ethical perspective resulted in the emergence of the idea of corporate social responsibility in the previous century. However, the destructive changes occurring in the natural environment caused by an overly expansive economy posed new challenges to business. They led to the birth of a new idea referring to the idea of sustainable development and the concept of a circular economy. Within its framework, principles were formulated for both business and consumers. Within the framework of the article, the authors set themselves two goals. The first was to indicate and strengthen the underestimated role of the consumer in the effective implementation of a circular economy, and the second was to indicate the role of companies not only in the implementation of the concept of a circular economy, but also in the area of educating their customers in this area (regardless of the dimension of individual or group actions of consumers).